Empowering adolescents in school settings: Basic life support and choking education - Syam, Aminuddin; Ibnu, Indra Fajarwati; Hasanuddin, Fitria; Anna, Andi Nur; Ernawati, Ernawati; Firawati, Firawati; Mantasia, Mantasia (Sociality: Journal of Public Health Service, 2025)
Previous studies have highlighted the importance of emergency preparedness in school settings. However, evidence on structured basic life support (BLS) and choking education among adolescents in rural and semi-rural areas remains limited, indicating a critical gap that this study addresses. This study aimed to improve the knowledge of junior high school students regarding basic life support and choking management at SMPN 4 Manggarabombang, Indonesia. A participatory educational intervention was implemented using an interactive lecture approach covering core concepts of BLS and choking management, followed by question-and-answer sessions and practical simulations to reinforce students’ understanding. The program involved 30 students, consisting of 8 males (26.7%) and 22 females (73.3%), predominantly aged 12–13 years. Knowledge levels were assessed using pre-test and post-test instruments. The results demonstrated a clear improvement in students’ knowledge following the intervention, with the mean pre-test score increasing from 5.03 to 6.87 in the post-test, representing an improvement of 1.84 points or 36.5%. The educational activity was well received by both students and school authorities, indicating high acceptability and feasibility of the program. These findings indicate that school-based BLS and choking education effectively improves adolescents’ emergency response knowledge while fostering preparedness and social responsibility through collaboration between universities, schools, and communities.